Trends in ophthalmology applicants going unmatched in the Canadian Resident Matching Service - Mostafa Bondok; Mohamed S Bondok; Christine Law; Nawaaz Nathoo; Karim F Damji (Canadian Medical Education Journal, 2023)
Background: Applicants to ophthalmology have high rates of going unmatched during the CaRMS process, but how this compares to other competitive or surgical specialties remains unclear. Our research aims to examine this phenomenon by identifying trends and comparing match data with other specialties, to identify disparities that may inform the need for future interventions to improve the match process for applicants.